The migrant-radicalisation Nexus : the case of blue-collar Bangladeshi migrant workers in Singapore - Nazneen Mohsina (2018)
The discovery of radicalised individuals among blue-collar Bangladeshi migrant workers in Singapore in 2015 and 2016 raises the question of why and how some individuals from this demography may embrace extremist ideologies. This thesis explores factors for their radicalisation by using both primary and secondary data. Primary data sources included informal interviews and writings by blue-collar Bangladeshi migrant workers in Singapore. Secondary data was collected based on content analysis of media reports, books, journals and other open source articles. I argue that various dynamics in the global and domestic environments of these workers interact and align to influence their radicalisation, and posit that their radicalisation is largely influenced by three sets of factors: (1) systemic factors such as advancements in communications technology, perception of subjugation, modern-day imperialism, accentuated identity as Muslims and solidarity with the ummah (global community of Muslims); (2) the religio-political dynamics in Bangladesh such as reduced democratic space, corruption and ineffective governance as well as perceived persecution; and (3) the environmental factors in Singapore such as material and immaterial forms of discrimination due to their nationality /identity and isolation from mainstream society. I contend that some blue-collar Bangladeshi migrant workers in Singapore become receptive to radical ideologies when their experiences resonate with the frames and narratives postulated by extremist movements, and are looking for justice and fairness, a clear sense of inclusion and purpose, and the opportunity to restore their dignity. I conclude with policy implications of my findings.